Relationships between Obesity, Cardiorespiratory Fitness, and Cardiovascular Function - Kade Davison; Stefan Bircher; Alison Hill; Alison M. Coates; Peter R. C. Howe; Jonathan D. Buckley (Journal of Obesity)
Background. Obesity and low cardiorespiratory fitness (CRF) have been shown to independently increase the risk of CVD mortality. The aim of this study was to investigate the relationship between CRF, body fatness and markers of arterial function. Method and Results. Obese (9 male, 18 female; BMI 35.3 ± 0.9 kg·m-2) and lean (8 male, 18 female; BMI 22.5 ± 0.3 kg·m-2) volunteers were assessed for body composition (DXA), cardiorespiratory fitness (predicted ̇VO2max), blood pressure (BP), endothelial vasodilatator function (FMD), and arterial compliance (AC) (via radial artery tonometry). The obese group had more whole body fat and abdominal fat (43.5 ± 1.2% versus 27.2 ± 1.6%; 𝑃<.001 and 48.6 ± 0.9% versus 28.9 ± 1.8%; 𝑃<.001, resp.), and lower FMD (3.2 ± 0.4% versus 5.7 ± 0.7%; 𝑃<.01) than the lean subjects, but there was no difference in AC. AC in large arteries was positively associated with CRF (R=0.5; 𝑃<.01) but not with fatness. Conclusion. These results indicate distinct influences of obesity and CRF on blood vessel health. FMD was impaired with obesity, which may contribute to arterial and metabolic dysfunction. Low CRF was associated with reduced elasticity in large arteries, which could result in augmentation of aortic afterload.